Cerebral blood flow and endothelial functional activity in patients with coronary heart disease and arterial hypertension during therapy with ivabradine in combination with perindopril - N A Musikhina (Терапевтический архив, 2012)
AIM: To investigate the effects of ivabradine in combination with perindopril on cerebral blood flow and endothelial functional activity. /MATERIAL AND METHODS: Sixty-four patients with coronary heart disease (CHD) and arterial hypertension (AH) were examined. Group 1 (n=38) patients took ivabradine in combination with perindopril and Group 2 (n=26) received metoprolol. At baseline and 8 weeks after therapy, 24-hour blood pressure (BP) monitoring and electrocardiography were done, cerebral blood flow was estimated by Doppler ultrasound, reactive hyperemia and nitroglycerin tests were performed, and plasma nitrite levels were determined /RESULTS: With a comparable decrease in BP and heart rate in the internal carotid artery basin in both groups over time, there was a fall in peak systolic blood flow velocity; Group 1 showed a reduction in pulsatility index (PI) and systolic/diastolic ratio (ISP). After 8 weeks, there was an increase in endothelium-independent vasodilation and baseline blood flow velocity in the brachial artery in Group 1 and a rise in endothelium-dependent vasodilation in Group 2; in both groups, reactive hyperemia were higher in the brachial artery basin. No changes in nitrite levels were recorded during therapy. There was an inverse correlation between PG and PI in Group 1 and between PG and ISP in Group 2 /CONCLUSION: By unidirectionally affecting the vasomotor function of the endothelium, ivabradine in combination with perindopril versus metoprolol has a more favorable effect on circulatory resistance and blood flow velocity in the brachiocephalic arteries of patients with CHD and AH.